1999
DOI: 10.1046/j.1440-1746.1999.01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer and gastritis in uraemia, with particular reference to the effect of Helicobacter pylori infection

Abstract: The prevalence of histological gastritis was lower in uraemic patients when compared with patients with functional dyspepsia and healthy volunteers. Peptic ulcers in uraemic subjects have different clinical characteristics from peptic ulcer in non-uraemic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 32 publications
5
36
1
1
Order By: Relevance
“…Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB. In addition, H. pylori infection has been associated with a higher risk of UGIB (23,24), and H. pylori eradication therapy decreases the risk of recurrent UGIB (25). Forty-two (1.4%) patients were receiving H. pylori eradication therapy; this therapy did not significantly affect UGIB risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB. In addition, H. pylori infection has been associated with a higher risk of UGIB (23,24), and H. pylori eradication therapy decreases the risk of recurrent UGIB (25). Forty-two (1.4%) patients were receiving H. pylori eradication therapy; this therapy did not significantly affect UGIB risk.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, previous studies have shown that the prevalence of H. pylori infection in patients with uremia is not higher than in the general population 6,23 and that H. pylori infection is not a risk factor for ulcer or recurrent ulcer in uremic patients. 14,24 Third, although smoking and alcohol consumption are risk factors for peptic ulcers, information about these factors was not available in the National Health Insurance dataset.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies on H. pylori infections in uremic patients have reported rates varying from 27% to 73.0% [12][13][14][15][16][17][18][19][20] . This variation may have been caused by small sample sizes, nonuniform duration of dialysis, and varying methodologies and enrollment criteria.…”
Section: H Pylori Prevalence Among Patients With End-stage Renal Dismentioning
confidence: 99%
“…pylori detection in patients with ESRD can be improved by performing the 13 C-urea breath test (UBT) after hemodialysis therapy and assessing the UBT with a cutoff excess 13CO2/12CO2 ratio value exceeding 5. However, the diagnostic efficacy of the UBT for patients with ESRD remains less accurate than that for dyspeptic patients without renal impairment.…”
Section: H Pylori Tests For Patients With End-stage Renal Diseasementioning
confidence: 99%